PERANAN RAJA JA’FAR YANG DIPERTUAN MUDA RIAU KE VI DALAM POLITIK KERAJAAN RIAU-LINGGA TAHUN 1806-1832 - Raja Rischa Dwi Lestari; Bedriati Ibrahim; Ahmal Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The Malay Kingdom of Riau Lingga is an Islamic kingdom located in the Riau Archipelago which was originally a territory including Johor, Pahang, this kingdom was formed based on the agreement of the United Kingdom (UK) and the Netherlands in 1824 with Sultan Abdurrahman Muazzamsyah as the first sultan of the Riau Lingga Kingdom. Then this is where the role of Yang Dipertuan Muda Riau began to participate in the government of the Kingdom of Riau Lingga as a representative of the sultan or Yang Dipertuan Besar of the kingdom. The purposes of this study are 1) To find out a brief history of the Riau-Lingga Malay Kingdom, 2) To find out how the process of revitalizing Raja Ja'far into YDPM VI, 3) To find out the role of King Ja'far in the politics of the Riau Lingga Kingdom in 1806- 1832, 4) To find out the role of the Bugis in the Riau Lingga Kingdom. The method used in this research is a qualitative approach method. The research location is in Tanjung Pinang, Riau Islands. The results showed the role of Raja Ja'far YDPM VI in the politics of the Riau Lingga Kingdom.Key Words: History, Riau Lingga Kingdom